2017
DOI: 10.1158/1538-7445.sabcs16-p6-16-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-16-04: Real World data and patterns of care of metastatic breast cancer (MBC) in Brazil: First results of LACOG 0312 retrospective study

Abstract: Background Randomised clinical trials (RCT) are considered a gold standard generating efficacy and safety data supporting drug approval. However, real world data (RWD) reflecting health care delivery is becoming increasingly important. RWD on patient profiles and patterns of care in MBC are scarce in developing countries. As an example, observational studies suggest that despite guideline recommendations clearly indicating ET for hormone receptor positive MBC, a considerable proportion of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…A prior retrospective observational study (LACOG 0312) reported a median OS of 34 months in patients diagnosed with MBC in 2012. 8 Furthermore, the median OS of the different subtypes of breast cancer resulted in comparable figures.…”
Section: Discussionmentioning
confidence: 91%
“…A prior retrospective observational study (LACOG 0312) reported a median OS of 34 months in patients diagnosed with MBC in 2012. 8 Furthermore, the median OS of the different subtypes of breast cancer resulted in comparable figures.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, most of the data on MBC originate from retrospective, hospital-based studies or controlled trials involving specific populations and treatments. 10,11,21,22 However, population-based studies have the advantage of enabling an epidemiologic analysis to be made of different populations, which may help in the development of specific public policies. 4,23,24 Therefore, the objective of the current study was to estimate OS and identify the prognostic factors associated with MBC in a Brazilian population for the period from 1995 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated the proportion of premenopausal patients and those presenting with de novo metastatic disease based on the results of the AMAZONA-I study. Moreover, other large Brazilian and international epidemiological studies and SEER data suggest reliability of our estimations [4,9,10,12,27,28]. Furthermore, the extrapolation of clinical trial results to the general population remains a challenging exercise.…”
Section: Discussionmentioning
confidence: 76%
“…The AMAZONA-I is a national epidemiologic study that followed a cohort of 634 MBC cases diagnosed in the year of 2012. It gathers data from private and public hospitals in different sites across the country [9,10]. The OSIS database imports and merges data from Hospital Cancer Registries and from DataSUS, Agência Nacional de Saúde and Instituto Brasileiro de Geografia e Estatística (all government agencies responsible for collecting national cancer information) building a national registry of cancer.…”
Section: Methodsmentioning
confidence: 99%